Animal model of arthritis and myositis induced by the Mayaro virus - Santos, Franciele Martins; Dias, Roberto Sousa; de Oliveira, Michelle Dias; Costa, Isabella Cristina Toledo Alves; Fernandes, Luciana de Souza; Pessoa, Carine Ribeiro; da Matta, Sérgio Luis Pinto; Costa, Vivian Vasconcelos; Souza, Danielle G.; da Silva, Cynthia Canêdo; de Paula, Sérgio Oliveira (PLOS Neglected Tropical Diseases, 2019)
Background The Mayaro virus (MAYV) is an endemic arbovirus in South American countries, where it is responsible for sporadic outbreaks of Mayaro fever. Clinical manifestations include fever, headache, ocular pain, rash, myalgia, and debilitating and persistent polyarthralgia. Understanding the mechanisms associated with MAYV-induced arthritis is of great importance due to the potential for its emergence, urbanization and dispersion to other regions. Methods 15-day old Balb/c mice were infected by two distinct pathways, below the forelimb and in the rear footpad. Animals were observed for a period of 21 days. During this time, they were monitored every 24 hours for disease signs, such as weight loss and muscle weakness. Histological damage in the muscles and joints was evaluated 3, 7, 10, 15 and 20 days post-infection. The cytokine profile in serum and muscles during MAYV infection was evaluated by flow cytometry at different post-infection times. For pain analysis, the animals were submitted to the von Frey test and titre in different organs was evaluated throughout the study to obtain viral kinetics. Findings Infection by two distinct pathways, below the forelimb and in the rear footpad, resulted in a homogeneous viral spread and the development of acute disease in animals. Clinical signs were observed such as ruffled fur, hunched posture, eye irritation and slight gait alteration. In the physical test, both groups presented loss of resistance, which was associated with histopathological damage, including myositis, arthritis, tenosynovitis and periostitis. The immune response was characterized by a strong inflammatory response mediated by the cytokines TNF-α, IL-6 and INF-γ and chemokine MCP-1, followed by the action of IL-10 and IL-4 cytokines. Interpretation The results showed that Balb/c mice represent a promising model to study mechanisms involved in MAYV pathogenesis and for future antiviral testing.